Extracting narratives from reality: Wang Bing's counter-narrative of the China Dream*. Issue 3 (2nd September 2017) - Pollacchi, Elena
ABSTRACT: Wang Bing's work provides a peculiar example of 'engaged filmmaking' without being openly oppositional towards the Chinese state. Although not easily included in the category of activist filmmakers, Wang Bing conveys political statements undermining the rhetoric of the People's Republic of China. From Tiexi qu. West of the Tracks (2003) on the dismissal of the industrial district in Liaoning, to Three Sisters (2012) and ' Til Madness Do Us Part (2013), both shot in remote areas of Yunnan, his cinema can be read as a corpus of works that address the contradictions imbued in the rise of China as a super-power. They bear witness to inequalities, uneven development and – as most of Wang Bing's documentaries do – also testify to the changing conditions of labor in China and their impact on people's lives. His recent Bitter Money (2016), shot in a large textile district of Zhejiang, takes labor as its focus and reaches one of the centers of China's wealth. Through a discussion of Wang Bing's filmmaking and the trajectory articulated by his documentaries, this article argues that Wang Bing's cinema provides a striking counter-narrative to the 'China Dream', the slogan that epitomizes the current leadership of Chinese President Xi Jinping.